Chemical requirements in Swedish municipal green public procurement: Challenges and opportunities. (25th May 2021) - Wendt-Rasch, Lina; Holmberg, Lars; Hagerman, Hélène; Breitholtz, Magnus; Ekman, Erika; Rudén, Christina
Abstract: Green public procurement has been identified as an important instrument to achieve the aim of substituting hazardous chemicals to more benign alternatives. Nevertheless, few studies have investigated the specific challenges associated with practically applying procurement requirements for reducing the content of hazardous chemicals. This study contributes with identifying and describing the specific challenges, improvement options, and conflicting goals relating to the aim of reducing exposure to hazardous chemicals through green public procurement. Graphical abstract: Image 1 Highlights: The complexity of chemical risks introduces particular challenges for procurement. Information and knowledge gaps severely hamper use of chemical requirements. Chemical requirements are rarely checked for follow-up compliance. Shortcomings weaken procurement as a policy instrument.